Heart rate recovery after a 60m sprint test is faster when VO2peak is high - Storniolo, J.; Minetti, A. E. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: The quick recovery of many physiological parameters is an important determinant of cardiorespiratory fitness (Coote, 2009). Particularly, oxygen consumption kinetics at the start and after intense dynamic exercise have been well explored (Borresen & Lambert, 2008), often in relation with the maximum aerobic power (V`O2peak). Less attention has been given so far to heart rate (HR) kinetics after maximal effort. We here use a simple test, a short sprint running, suitable to check the relationship between a speed index of heart rate recovery, namely the time interval to reach 50% of the difference with the basal HR ( off-HRsprint, s) and V`O2peak in active and sedentary subjects. Methods: Sixteen individuals subdivided in sedentary (SED, n=8; 26.3±8.0 years, 72.1±12.6 kg, 174.0±12.5 cm) and active (ACT, n=8; 25.4±3.5 years, 68.5±6.0 kg, 178.0±7.2 cm) undertook both a 60-m sprint test on firm terrain to obtain off-HRsprint by sampling HR recovery in orthostatism and, after 10 min rest, an incremental cardiopulmonary test on a treadmill to determine the V`O2peak and V`O2 off kinetics ( off-V`O2, s) defined similarly as for HR. A Student`s t test checked differences in SED and ACT groups among off-HRsprint, off-V`O2 and V`O2peak. A Pearson`s product-moment test was used to assess correlation between variables. Results: When compared to SED, ACT group presented significantly higher values for V`O2peak (p<0.001) and lowered for off-HRsprint (p=0.006), whereas off-V`O2 was similar in the two groups (p=0.702). When considered separately SED e ACT groups did not show significant pairwise correlations among off-HRsprint, off-V`O2 and V`O2peak. Differently, when pooling all subjects, off-HRsprint and V`O2peak showed a significant correlation (r=-0.64, p=0.008). Discussion: off-V`O2 was similar between groups despite of different training levels, although off-V`O2 depends on several factors, as mitochondrial density, oxidative enzyme activity and lactate removal, which are likely affected by training (Dupont et al., 2010). The off-HRsprint and V`O2peak did show significant (negative) correlation only when all subjects data were pooled, indicating that HR variability needs a high sample size to reveal reliable relationships with V`O2peak. The present analysis of HR recovery has the potential to indirectly estimate individual V`O2peak. Further studies involving different sample sizes, heart rate off-kinetics at shorter maximal tests, as well as other groups of subjects, could check the stability of the obtained parameters and refine its applied physiological relevance.